On diffusion of chemically reactive species in a convective flow past an inclined plate with variable surface temperature and variable mass diffusion - Kirubavathi, J. D.; Palani, G. (Zielona Góra: Uniwersytet Zielonogórski)
A numerical solution of a transient natural convection flow past a semi-infinite inclined plate under the combined buoyancy effects of heat and mass transfer along with chemical reaction is presented herewith. The governing boundary layer equations for the above flow problem for a first order homogeneous chemical reaction are set up and non-dimensionalised. An implicit finite difference method is employed to solve the unsteady, non-linear, integro and coupled partial differential equation. Numerical results are presented for various parameters occurring in the problem. The unsteady velocity, temperature and concentration profiles, local and average skin friction, Nusselt number and Sherwood number are studied for both a generative and destructive reaction.
Keywords: chemically reactive species; finite-difference method; inclined plate; skin friction and Nusselt number